Aflatoxin M1 Levels in Surk Samples, a Traditional Turkish Cheese from Southern Turkey - Aygun, Osman; Essiz, Dinc; Durmaz, Hisamettin; Yarsan, Ender; Altintas, Levent (Springer, 2009)
In this study, aflatoxin M-1 (AFM(1)) contamination was investigated in Surk cheese, a traditional Turkish cheese consumed particularly in southern Turkey. For this purpose, 120 Surk cheese samples were collected from different retail markets and analysed by enzyme-linked immunoassay. The level of AFM(1) varied from 16 to 1,043 ng/kg in 72 of the Surk samples (60%), 16 of which (13.3% of 120 samples) contained AFM(1) amounts exceeding the maximum tolerance limit (250 ng/kg) established in Turkey. The results indicated that the occurrence of AFM(1) in Surk cheese samples may be considered as a possible risk for consumer health.
Keywords: Aflatoxin M-1; Surk; Cheese; ELISA